1990
DOI: 10.1104/pp.94.4.1512
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Membrane Lipid Composition during Saline Growth of the Fresh Water Cyanobacterium Synechococcus 6311

Abstract: Growth of Synechococcus 6311 in the presence of 0.5 molar NaCI is accompanied by significant changes in membrane lipid composition. Upon transfer of the cells from a 'low salt' (0.015 molar NaCI) to 'high salt' (0.5 molar NaCI) growth medium at different stages of growth, a rapid decrease in palmitoleic acid (C16:1A9) content was accompanied by a concomitant increase in the amount of the two C18:1 acids (C18:1A9, C18:IAI1), with the higher increase in oleic acid C18:1A9 content. These changes began to occur wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 26 publications
3
30
0
3
Order By: Relevance
“…The ratio of saturated and unsaturated fatty acids and the phospholipid composition of membranes are critical factors in this regard (Nishida and Murata 1996;Sakurai et al 2003Sakurai et al , 2007. When photosynthetic organisms are exposed to salt stress, fatty acids of membrane lipids are desaturated (Huflejt et al 1990). Therefore, it is possible that unsaturation of fatty acid in membrane lipids might affect the tolerance of the photosynthetic machinery to salt stress.…”
Section: Unsaturation Of Fatty Acids In Membrane Lipids Increases Thementioning
confidence: 98%
“…The ratio of saturated and unsaturated fatty acids and the phospholipid composition of membranes are critical factors in this regard (Nishida and Murata 1996;Sakurai et al 2003Sakurai et al , 2007. When photosynthetic organisms are exposed to salt stress, fatty acids of membrane lipids are desaturated (Huflejt et al 1990). Therefore, it is possible that unsaturation of fatty acid in membrane lipids might affect the tolerance of the photosynthetic machinery to salt stress.…”
Section: Unsaturation Of Fatty Acids In Membrane Lipids Increases Thementioning
confidence: 98%
“…The content and activity of LeGPAT were higher in sense plants than in WT, and the increase of cis-unsaturated fatty acids in PG enhanced the tolerance to low temperature in tomato (Sui et al 2007b). When photosynthetic organisms are exposed to salt stress, fatty acids of membrane lipids are desaturated (Huflejt et al 1990). By comparing desA -/desD -mutant cells with WT cells, Allakhverdiev et al (1999) found that the function of unsaturation of fatty acids in membrane lipids enhanced the tolerance of Synechocystis cells to salt stress.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on Synechocoecus grown in the presence of 0.5 M NaCl revealed that salinity has also considerable effects on fatty acid and lipid composition of thylakoid Mineral deficiency membranes (Huflejt et al 1990). On the other hand Mineral deficiencies are mainly caused by the quality of pre-treatment of barley plants with 100 mM NaCl inthe soil which in turn is determined by the rocky subsoil, creased the resistance of isolated thylakoids to an even Older forms of agriculture as well as emissions of acid more severe salinity (1 M NaCl) stress as measured by air pollutants such as S02and NO2 have accelerated the oxygen evolution rate (Maslenkova et al 1993).…”
Section: Stress Conditionsmentioning
confidence: 99%